Ligand-promoted intramolecular dehydrogenative cross-coupling using a Cu catalyst: direct access to polycyclic heteroarenes - Ray, Devalina; Manikandan, T.; Roy, Arup; Tripathi, Krishna N.; Singh, Ravi P. (Chemical Communications, 2015)
A copper(II)-promoted intramolecular C-H coupling reaction between indole-2 and imidazole-2 moieties has been developed for polycyclic heteroarene synthesis. The method provides direct access to biheteroaryl incorporated polycyclic frameworks, which are of huge interest in the area of functional materials and drug-discovery.